Penyuluhan Hukum Mengenai Hak Warga Masyarakat Yang Terlibat Masalah Hukum Pada Kelurahan Benteng - Nugrah Gables Manery; Johan Pieter Elia Rumangun; Dita Ayudia Pratiwi; Harly Clifford Jonas Salmon; Armelia Febryanty Waas (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
The low level of understanding of the community members in general regarding the provisions regarding fundamental rights attached to community members when involved in legal issues, the purpose of this legal counseling is to provide knowledge and understanding of the law, especially the provisions concerning the rights of community members when involved in legal issues. The method used in this legal counseling is the lecture and discussion method. The result of this legal counseling is to increase legal knowledge and awareness, legal counseling must be carried out periodically with additional material on law enforcement, both preventive and repressive.